Minat Wirausaha Siswa Pendidikan Vokasi dalam Bidang Jasa Instalasi Penerangan Listrik - Doni Tri Putra Yanto; Ganefri Ganefri; Asmar Yulastri; Hermi Zaswita; Maryatun Kabatiah (Universitas Negeri Padang, 2023)
This study discusses the analysis of the entrepreneurial interest of vocational education students in the field of electric lighting installations. Science competence in Electrical Lighting Installation Engineering owned by vocational education graduates can be one of the basic opportunities for entrepreneurship while still paying attention to the factors that influence it. The factors that influence entrepreneurial interest come from internal and internal factors. This study aims to reveal studentsâ€™ entrepreneurial interest in Electrical Lighting Installation Engineering at State Vocational High School (SMKN) 1 West Sumatra in terms of internal and external factors. Quantitative research with a descriptive approach is applied to 37 students of class XI and XII, the competency of Electrical Lighting Installation Engineering as a research subject. The questionnaire was used as an instrument for collecting research data which was then processed using the SPSS application to obtain the percentage value of the respondents' achievement for interest in entrepreneurship. The results showed that when viewed from internal and external factors, the percentage of Respondents' Achievement Level (TCR) for entrepreneurial interest was in the high category, and if reviewed separately internal factors affecting entrepreneurial interest were in the high category, while external factors affecting student entrepreneurial interest were enough category. Thus, it can be concluded that the entrepreneurial interest of students in the Electrical Lighting Installation Engineering Skills competence is in the high category and internal factors are factors that have a high influence.Â